Design, Synthesis, Characterization and Antiproliferative Activities of Ru(II) Complexes of Substituted Benzimidazoles - Singh, Ashok K.; Katheria, Snehlata; Kumar, Amrendra; Zafri, Asiff; Arshad, Mohd. (Asian Journal of Chemistry, 2019)
Synthesis of [Ru(PPh3)2(BZM)2Cl2] (BZM= LS1, LS2, LS3, LS4 and LS5) where LS1 = (1H-benzo[d]imidazole-2-yl)methanethiol, LS2 = 2-(4-bromobutyl)-1H-benzo[d]imidazole, LS3 = 2-(4-nitrophenyl)-1H-benzo[d]imidazole, LS4 = 2-(4-chlorophenyl)-1H-benzo[d]imidazole and LS5= 4-(1H-benzo[d]imidazol-2-yl)aniline (BZM = benzimidazoles, PPh3 = triphenylphosphine) and metal complexes as MR, [ Ru(PPh3)4Cl2], MLS1, MLS2, MLS3, MLS4 and MLS5 for use as potential anticancer compounds have been investigated. The complexes have been characterized by elemental analysis, IR, multinuclear NMR, UV-visible and ESI-MS spectroscopic techniques. The geometries of all complexes have been optimized by using density functional theory (DFT). The cytotoxicity effects of MR, MLS2 and LS1 were also investigated on Human cervical carcinoma cells (HeLa) by MTT assay, ROS generation and nuclear apoptosis assay. The percent cell viability assessed by MTT assay suggested that the synthesized MR, MLS2 and LS1 significantly reduce the viability of HeLa cells, in a dose-dependent manner. The inhibitory concentration (IC50) of MR, MLS2 and LS1 against HeLa cells was found 90.8, 81.8 and 115 μM, respectively. These compounds also induced the over production of intracellular reactive oxygen species (ROS) as well as the condensed and fragmented nucleus, which supports the molecular mechanism of cell death by apoptosis. The investigations suggested that the compounds MR, MLS2 and LS1 induce the cell death in HeLa cells through apoptotic pathway.